5 - Navigating the Uncertain Path of Research Partnerships: The Role of ICT - Boateng, John Kwame; Tutu, Raymond Asare (Journal of Higher Education in Africa, 2022)
In this article, we share experiences of the nature of an infant collaboration and how information and communication technology (ICT) is at its heart. We situate our discussion in the broader discourse surrounding educational research collaboration. The main issues we address are: (i) the peculiar nature of our collaboration; (ii) the main collaboration stimuli; (iii) the anticipated benefits and costs of the collaboration; and (iv) the role of ICT. We show that while ICT is invaluable to our collaborative work and its future prospects, it requires a great deal of commitment to nurture, grow and maintain. Although the initial objective of our research network is to examine how technology mediates student–instructor interaction, through ICT we are moving the frontiers of this collaboration to other areas of expertise, interest and strength. Through the log of our communication via Skype, WhatsApp, phone calls and other channels, we demonstrate how beneficial ICT is to our collaboration. We conclude with other possible forms that this network could take and emerge into, given the composition of the research network.